Chondroitin sulfate-modified tragacanth gum–gelatin composite nanocapsules loaded with curcumin nanocrystals for the treatment of arthritis - Junpeng Sun; Jiaqun Du; Xiaobang Liu; Jinyu An; Yu Hu; Jing Wang; Fu Zhu; Huicong Feng; Shuai Cheng; He Tian; Xifan Mei; Chao Wu (Journal of Nanobiotechnology, 2024)
Abstract Rheumatoid arthritis (RA) is a chronic autoimmune disease of yet undetermined etiology that is accompanied by significant oxidative stress, inflammatory responses,  and damage to joint tissues. In this study, we designed chondroitin sulfate (CS)-modified tragacanth gum–gelatin composite nanocapsules (CS-Cur-TGNCs) loaded with curcumin nanocrystals (Cur-NCs), which rely on the ability of CS to target CD44 to accumulate drugs in inflamed joints. Cur was encapsulated in the form of nanocrystals into tragacanth gum–gelatin composite nanocapsules (TGNCs) by using an inborn microcrystallization method, which produced CS-Cur-TGNCs with a particle size of approximately 80 ± 11.54 nm and a drug loading capacity of 54.18 ± 5.17%. In an in vitro drug release assay, CS-Cur-TGNCs showed MMP-2-responsive properties. During the treatment of RA, CS-Cur-TGNCs significantly inhibited oxidative stress, promoted the polarization of M2-type macrophages to M1-type macrophages, and decreased the expression of inflammatory factors (TNF-α, IL-1β, and IL-6). In addition, it also exerted excellent anti-inflammatory effects, and significantly alleviated the swelling of joints during the treatment of gouty arthritis (GA). Therefore, CS-Cur-TGNCs, as a novel drug delivery system, could lead to new ideas for clinical therapeutic regimens for RA and GA. Graphical Abstract